Pendidikan Sosial dan Kemanusiaan dalam Al-Qur’an - Muhamad Zikri; Tita Yunita; Parlindungan Simbolan (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
One of the issues raised is about social changes in society, namely how a person must respond to these changes in order to be able to carry them out according to the teachings of the Qur'an. As part of a complex community of ever-changing and dynamic social individuals, society is not something fixed or stagnant. This is due to the fact that people experience various social relationships through social processes that occur due to living together. Interaction between individuals, cultural developments, and the dynamics of social values and norms also affect the way people view their daily lives. In this context, the Qur'an provides moral and ethical guidelines that can be the foundation for building harmonious and just social relationships. Values such as care, justice, social responsibility, and respect for fellow human beings are important principles emphasized in the teachings of the Qur'an. Therefore, social education based on the values of the Qur'an has an important role in shaping individual character to be able to adapt to social changes without abandoning moral and humanitarian principles. Given the importance of this issue related to social education, the author argues that research on social education will delve into this topic with a focus on social education based on the Qur'an.